The development of children - Cole, Michael (Scientific American Books Distributed by W.H. Freeman, 1993)
This book presents the science of child development without losing sight of the child. Its emphasis on cultural context, integration of the diverse aspects of development, authoratitive presentation of competing theories, and scientific integrity combine to form a high standard of text. The second edition offers, greater accessibility, more balanced coverage, and new full-colour art, featuring photographs from a variety of cultures. Significant revisions include earlier and clearer treatment of infancy; expanded discussion of middle childhood; new coverage of topics such as the development of emotion, theory of mind, and ethnic identity. Ancillary texts include an instructors manual with test questions, a study guide, computerized test banks (for MAC and IBM), overhead transparencies and a book of readings.